Social Alienation in the Digital Age: Roland Barthes' Semiotic Analysis of The Meaning of 'Ghaflah' in Qs. Al-A'raf Verse 205 - Akhmad Dasuki; Rian Hidayat; Marwa; Shafa; Siti Mudthiya Arpijayanti; Cecep Zakarias El Bilad (Medina-te : Jurnal Studi Islam, 2026)
This study explores the concept of ghaflah in Surah Al-A'raf verse 205 as an entry point to examine the phenomenon of social alienation in the digital age through Roland Barthes' semiotic approach. The term ghaflah, which literally means negligence or forgetfulness, is analysed on two levels: denotative (literal meaning) and connotative (symbolic/ideological meaning). The main research questions focus on how ghaflah is interpreted semiotically and whether its meaning is relevant to current social phenomena such as doomscrolling, digital alienation, and collective awareness crises. The objective of this study is to uncover the hidden meanings of ghaflah and explain how the concept reflects the socio-psychological conditions of modern society. This research employs a qualitative-descriptive method based on literature review, using Barthes' semiotic theory as the primary analytical framework. Core references include Tafsir al-Misbah, Lisan al-‘Arab, semiotic literature, and contemporary studies on digital media. The analysis is conducted in two stages: (1) interpreting the literal meaning of ghaflah using exegetical and linguistic sources, and (2) extracting the connotative meaning through Barthes' framework to uncover its ideological and mythological dimensions. The findings show that ghaflah is not merely spiritual negligence but also a metaphor for modern human alienation caused by the domination of technology and digital media. In this context, ghaflah functions as a sign of existential, spiritual, and social crises deeply rooted in contemporary life patterns. In conclusion, Surah Al-A’raf: 205 is not only theologically significant but also offers a critical reflection on the destructive impacts of the digital era on human consciousness, meaning, and spiritual values.